Avaliação de diferentes processos de secagem de subprodutos do processamento de maracujá (Passiflora edulis) e caracterização do produto seco obtido - Oliveira, Nayara Maria de (2024)
The yellow passion fruit (Passiflora edulis Sims) is a fruit of highly nutritious and rich, rich in minerals and bioactive compounds. However, its industrial processing generates a significant amount of waste, mainly peels, and seeds, which can account for up to 70% of the total fruit weight. These by-products have great potential for reuse, with dehydration being an effective method to reduce moisture content, extend chemical and microbiological stability, and enable their incorporation into food and nutraceutical formulations. Various drying techniques have been employed to preserve food and agro-industrial by-products. Convective oven drying stands out, among conventional methods while alternative approaches, such as cast-tape drying, are being investigated to optimize the retention of bioactive compounds. In this context, this study aimed to evaluate the drying efficiency of passion fruit residues using three different processes: convective oven drying, cast-tape drying, and freeze-drying. The study also sought to characterize fresh and dehydrated samples for each method and compare the results with commercial passion fruit peel flour. The drying experiments using cast-tape drying and convective oven drying with air circulation were conducted at 65, 75, and 85 °C, with residue thicknesses of 2, 3, and 4 mm. The initial moisture content of the fresh residues was, on average, 70.11% (wet basis). To reach a final moisture content of 10%, the drying times in cast-tape drying were shorter than those in convective drying under the same experimental conditions, indicating higher process efficiency in moisture removal. The analysis of bioactive compounds revealed that all drying methods could preserve these constituents, with certain conditions yielding higher levels than those found in the commercial passion fruit peel flour. The results of this study demonstrate that cast-tape drying represents a promising alternative for the reutilization of by-products from the industrial processing of passion fruit pulp, contributing to the valorization of these residues and the reduction of waste in the agro-industrial sector.